PENGARUH SISTEM PENGENDALIAN INTERN, PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN RUMAH SAKIT UMUM DAERAH KABUPATEN BOYOLALI - Lusi Putri Ikasari, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this research is to analyze the significance of the influence ofthe system of internal control, understanding Government accounting standards andcompetencies of human resources to the quality of financial reporting. This researchis a survey of Hospitals in Boyolali Regency. Population and sample research is theOfficial Structural Non medical General Hospital Area and Boyolali district as muchas 39 people. The data type using the data qualitative and quantitative data. Datasource using primary data and secondary data. Method of data collection using thequestionnaire and the study of the literature data analysis techniques using multiplelinear regression. The results showed that the system of internal control,understanding Government accounting standards and competencies of humanresources for positive and significant effect of the quality of financial reportinginformation the Provincial Hospital in Boyolali Regency. The result of thedetermination coefficient obtained value Adjusted R2 = 0.808 means the influence ofthe internal control system variables, understanding Government accountingstandards and competencies of human resources to the quality of the financialstatements is 80.8% While amounting to 19.2% is affected by other factors notexamined, such as the control of management.Keywords: internal control systems, understanding government accountingstandards, the competence of human resources, the quality of financialreporting.